SYSTEM OF INDICATORS FOR ASSESSING PERFORMANCE EFFICIENCY OF HIGHER EDUCATION INSTITUTIONS: Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
This article focuses on the issues of evaluating the effectiveness of higher educational institutions and improving the educational process and quality based on it, further developing the educational material and technical base at the level of modern requirements. Also, using the results of the calculation of quality indicators developed for the evaluation of the efficiency of higher education institutions, scientifically based conclusions and suggestions are given on the elimination of existing problems and shortcomings in the institutions.